Intuitionistic Fuzzy TOPSIS Method Based on Improved Score Function and Cumulative Prospect Theory - LIU Huan; LI Hao (Journal of Harbin University of Science and Technology)
Aiming at the multi-attribute decision-making problem where the attribute value is represented by the intuitionistic fuzzy number and the attribute weight is unknown.Firstly, an improved score function is proposed, its correctness and superiority are verified by proving its related theorems and comparing numerical examples with existing score functions.It solves the defects that the existing score function requires secondary comparison and is inconsistent with objective facts in some cases.Secondly, the cumulative prospect theory is introduced, and a TOPSIS method for intuitionistic fuzzy multi-attribute decision-making based on improved score function and cumulative prospect theory is proposed.This method uses the positive and negative ideal alternatives as a reference point.The comprehensive prospect value is used to replace the distance measure, which effectively avoids ignoring the correlation between attributes.The order of alternatives is listed by calculating the relative closeness degree of each alternative.Finally, the feasibility and effectiveness of the proposed score function and decision-making method are verified by comparing examples and simulation data with existing decision-making method.